STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN KARAKTER PESERTA DIDIK KELAS VIIIA DI SMP NEGERI 7 CENRANA KABUPATEN MAROS: Penelitian Kualitatif - mira rahmayani; mustamin; Muh. Azhar Burhanuddin; Ahmad; Ratika Nengsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) describe the profile of students in character development of class VIII A at SMPN 7 Cenrana, Maros Regency; 2) describe the strategies used by Islamic Religious Education (PAI) teachers in character development of class VIII A students at SMPN 7 Cenrana, Maros Regency; and 3) identify the supporting and inhibiting factors of the PAI teachers’ strategies in character development of class VIII A students at SMPN 7 Cenrana, Maros Regency. The method used in this study is qualitative research. The subjects of the study were students of class VIII A, Islamic Religious Education teachers, and students of SMP Negeri 7 Cenrana. Data collection methods included observation, interviews, and documentation. Based on the results, character development of class VIII A students at SMPN 7 Cenrana was conducted through intrakurricular, co-curricular, and extracurricular activities. Intracurricular activities instill moral values through academic subjects, while co-curricular activities strengthen character understanding through direct practice. Extracurricular activities serve as a platform for developing discipline, responsibility, and teamwork. Islamic Religious Education teachers applied strategies such as advice, habituation, modeling, and discipline cultivation in shaping student character. Supporting factors included a religious school environment, parental support, and community culture. Obstacles faced involved limited variety in teaching methods and less supportive family backgrounds. Keywords: Strategy, Islamic Religious Education Teacher, Character, Devel.